Middle Cerebral Artery Thrombectomy: Clinical Findings and Technical Pearls: 2-Dimensional Operative Video. Issue 2 (16th April 2021) - Rangwala, Shivani D; Selvan, Pradeep; Tenser, Matthew; Mack, William; ,
Abstract: Mechanical thrombectomy as a treatment for large vessel occlusion to achieve rapid revascularization is supported in the literature. 1-3 The presenting symptoms will localize to functions of the ischemic area. The middle cerebral artery (MCA) supplies areas of the frontal, temporal, and parietal cortices, as well as the basal ganglia. Occlusion of the MCA will present with contralateral hemiplegia, sensory loss, and, if the dominant hemisphere is involved, language deficits. We present a right-hand-dominant 79-yr-old female with right MCA syndrome—her last known well time was 1.5 h prior to presentation. Her NIH (National Institutes of Health) Stroke Scale was 16, most notable for left hemiplegia. Although the patient presented early in the clinical time course, as part of our institution protocol, a computed tomography (CT) head, CT perfusion, and CT angiogram (CTA) were performed. CT head did not demonstrate acute hemorrhage, so she received intravenous tissue plasminogen activator. CTA demonstrated a right MCA occlusion and CT perfusion suggested a large area of salvageable tissue, so she was taken to the angiography suite for mechanical thrombectomy. Angiography of the right internal carotid artery (ICA) showed MCA occlusion (insular segment). A thrombectomy device was deployed over the area of occlusion and allowed to engage for 5 min. An aspiration catheter was advanced over the stentriever up against the clot. The stentriever device was withdrawn under continuous aspiration and follow-up angiography showed complete reperfusion. The patient demonstrated improvement and was eventually discharged to an inpatient rehabilitation center. Patient provided consent for photography per university protocol. Institutional review board (IRB) approval was not needed for the single-patient data included in this report.